Sintesis Silika Mesopori Sba-15 Dari Abu Daun Jagung (Zea Mays L) - Nasri Nasri; R R Dirgarini J. N Subagyono; Rahmat Gunawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
The synthesis and characterization of mesoporous silica Santa Barbara Acid-15 (SBA-15) from the ash of corn have been done. SBA-15 was synthesised using the surfactant template method. SBA-15 from corn leaves ash has a surface area of 592 m2 / gram, pore volume of 0.99 cm3 / gram and pore diameter of 3.95 nm with pore size ranging from 4.9 nm - 7.1 nm. The SAXS pattern of the bio-SBA-15 showed three typical peaks of SBA-15 with miller indices [100], [110] and [200]. In the FTIR spectrum of SBA-15, peaks from Si-O-Si, Si-OH and H-O-H from water were observed.